The Urgency of the Fifth Amendment to the 1945 Constitution of the Republic of Indonesia: Reconstructing People’s Sovereignty from a Constitutional Law Perspective - Rinto Setiyawan; Alessandro Rey Nearson; Prayogi Restia Saputra (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Constitutional amendment is a central mechanism for adapting a living constitution to social, political, and legal dynamics. Specific Background In the Indonesian constitutional framework, the post-amendment formulation of Article 1 paragraph (2) affirms that sovereignty lies in the people and is exercised according to the Constitution, yet public participation remains largely limited to electoral mechanisms. Knowledge Gap The existing constitutional arrangement has not fully translated people’s sovereignty into substantive participation, balanced institutional authority, and direct public control beyond elections. Aims This study examines the urgency of the fifth amendment to the 1945 Constitution in reconstructing people’s sovereignty from the perspective of constitutional law. Results The analysis shows that the fifth amendment is constitutionally possible under Article 37 and is directed toward strengthening participatory democracy, good governance, institutional balance, and clearer mechanisms for public involvement through referendum, legislative petitions, and direct oversight. The study also identifies the need to reposition the MPR as a balancing institution, clarify the separation of state functions, and address regulatory gaps in response to contemporary legal needs. Novelty The article offers a people-centered constitutional reconstruction model that combines MPR deliberation, public initiative, constitutional review, and possible referendum mechanisms. Implications A carefully designed and inclusive amendment process can deepen democratic substance, restore public legitimacy, and ensure that state authority operates for public welfare. Highlights: Public involvement remains largely confined to elections rather than substantive decision making. MPR positioning, checks and balances, and interinstitutional functions require clearer design. Referendum, legislative petitions, and direct oversight are proposed as channels for citizen control. Keywords: Constitutionalism; Sovereignty, Referendum, Governance, Democracy